Preparing potato for climate change: Breeding, selection and efficient use of genetic resources for abiotic stress - Amoros, W.; Cabello, R.; Gutiérrez, R.; Kadian, M.S.; Carli, C.; Salas, E.; Munive, S.; Bonierbale, Merideth W. (Springer, 2012)
Due to the implications that climate change will no doubt have on potato yields and production patterns, CIP’s breeding program is developing new generations of broad-based disease resistant populations better-adapted to drought and heat. More than 300 clones and selected progenies were evaluated under water-limiting and high temperature conditions in the desertic coast of Peru and in India, Bangladesh, Uzbekistan and Tajikistan. Elite clones with high yield indexes and superior progenitors of stress tolerance were identified and information incorporated for collaborative breeding across environments. Meanwhile, in order to assess wider diversity of cultivated potatoes, a set of 918 potato accessions including landraces, improved varieties and advanced breeding material has been evaluated under full and limited irrigation conditions in Peru. Significant differences were found for tuber yield, tuber number and tuber size among accessions and cultivar groups in both treatments. Early generation screening methods were developed to screen new families for heat tolerance under in vitro conditions targeting ability to tuberize at 25°C night and 19°C day temperatures. Physiological parameters and drought tolerance mechanisms have been studied in complementary approaches: Evaluation of water use efficiency toward the identification of tolerance to dehydration revealed differences in transpiration efficiency and conductance; and evaluation of survival under drought, permitted the identification of genotypes with high osmotic adjustment. The use of remote perception tools such as infrared thermometer, reflectance, infrared camera, measuring NDVI indexes and canopy temperature, is combined with germplasm evaluation and assist and accelerate screening and breeding for drought tolerance.